Fine particulate matter from pig house induced immune response by activating TLR4/MAPK/NF-κB pathway and NLRP3 inflammasome in alveolar macrophages. (December 2019) - Tang, Qian; Huang, Kai; Liu, Junze; Wu, Sheng; Shen, Dan; Dai, Pengyuan; Li, Chunmei
Abstract: Fine particulate matter (PM2.5 ) from livestock houses is harmful not only to the health and welfare of animals but also to the farmers working inside. As an important pollution source in the atmosphere environment, PM2.5 can threaten public health. PM2.5 collected from nursery pig house was studied. It included particulates of various morphologies, and the concentration of endotoxin was as high as to 681.80 EU/mg. To investigate the ability of PM2.5 from the nursery pig house to induce an immune response, porcine alveolar macrophages 3D4/21 cells were studied. The results showed that PM2.5 can induce cell death, ROS production and inflammatory cytokines release (IL-1β, IL-18, TNF-α and COX-2) by activating TLR4/MyD88 pathway and NLRP3 inflammasome. Furthermore, the downstream signaling pathways of TLR4/MyD88, MAPK and NF-κB, participated in NLRP3 inflammasome activation. To further study the role of endotoxin present in PM2.5 and the oxidative stress induced by PM2.5, polymyxin B (PMB) and N-acetylcysteine (NAC) were used to neutralize the effect of the endotoxin and inhibit the production of ROS, respectively. The results showed endotoxin and ROS played important roles in PM2.5 -induced immune response. This study suggests that PM2.5 from pig house is a significant risk for immune response in alveolar macrophages. Graphical abstract: Image 1 Highlights: The concentration, morphology and chemical components of PM2.5 were investigated. PM2.5 can activate TLR4 and NLRP3 inflammasome in 3D4/21 cells. MAPK and NF-κB pathways participated in NLRP3 inflammasome activation. Both endotoxin and ROS play vital roles in PM2.5 -induced immune response.